Probing the Tz=−3/2 nuclei via magnetic moment measurements - Mertzimekis, T. J. (HNPS Advances in Nuclear Physics, 2020)
The neutron-deficient region of the nuclear chart provides unique opportunities to study several important effects near the proton-drip line pertaining to nuclear structure and nuclear astrophysics. The present article focuses on nuclei with isospin Tz=−3/2 in terms of the spin polarization and the ground state magnetic moment. An experiment on measuring the ground state moment pf 35K by employing the β-NMR technique leads to several interesting results that pose challenging questions to theory.